Peranan Kepuasan sebagai Mediasi dalam Pengaruh Kualitas Produk dan Harga terhadap Loyalitas Pelanggan Lipstik Sariayu - Dhica Rachmawati (UNESA In Collaboration With APSMBI (Aliansi Program Studi dan Bisnis Indonesia), 2021)
The Indonesian cosmetics industry is currently developing”one of them, PT. Martina Berto encourages her company to excel in competition. The first brands produced and marketed was Sariayu Martha Tilaar as a natural cosmetics. In 1983, Sariayu had become a very well-known cosmetics in the country. PT. Martina Berto, developed by Martha Tilaar Group, improves the quality of Sariayu lipstick products and maintains affordable prices so that it can compete with other lipstick products. The purpose of this study is to analyze and discuss the effect of product quality and price on loyalty with satisfaction as an intervening variable on SARIAYU Lipstick customers at Martha Tilaar Tunjungan Plaza Surabaya Outlet. This type of research is quantitative research. This research uses a non-probability sampling technique with 110 respondents taken from SARIAYU Lipstick customers at Martha Tilaar Tunjungan Plaza Surabaya Outlet. The instrument used was a questionnaire that used a Likert scale and analyzed it with path analysis using AMOS 22. The results showed a positive and significant effect of product quality on satisfaction. There is also a significant effect of price on satisfaction. Then there is a positive and significant effect of satisfaction on loyalty. Besides, there is a positive and significant effect of product quality on loyalty. Furthermore, finally, there is a positive and significant price on loyalty.